Innovation in secondary education: The role of ICT in the evolution of learning processes - Tubay Moreira, Máximo Fernando (2026)
This research analyzed the relationship between innovation in secondary education and the use of information and communication technologies (ICTs) among third-year high school students, as well as their influence on learning processes. A mixed methodology with a qualitative and quantitative approach was employed, through the application of surveys to 150 students and 20 teachers from the educational institution.   The research findings revealed similarities in the explicit use of these tools and their contribution to learning innovation through strategies, programs, and applications. However, differences were identified between the perceptions of students and teachers when describing the effectiveness of these technologies in school methods. It is concluded that ICTs allow teachers to achieve objectives within the educational context, provided there is awareness and appropriate management of the available resources. Furthermore, the importance of providing a comprehensive education to adolescents in a world marked by information and digital knowledge is highlighted, a world that demands continuous learning and updating to avoid falling behind.